ANALISIS BENTUK DAN FUNGSI KALIMAT IMPERATIF DALAM FILM TOP GUN: MAVERICK - Septiaji, Faisal; Sudibiyo, Safina Rihhadatul áisy; Sumarlam, Sumarlam (Translation and Linguistics (Transling), 2023)
The Top Gun: Maverick is an action movie that was released in 2022 and directed by Joseph Kosinski. This movie tells the story of Pete “Maverick” Mitchell, performing ground-breaking stunts as a daring test pilot, and turning down every opportunity to get promoted because it would prevent him from flying his plane. Since this is an action movie and the set is about US Navy, many characters use imperatif sentences includes command, request, warning, and invitation. This research aims to explain the form and the function of imperatif sentences in the Top Gun: Maverick (2022) movie. The data research was taken from its subtitle and using observing method to analyzes it. The researcher use Aarts and Aarts (1982) theory to analyze the form and the function of imperatif sentences from the movie. The result is imperatif sentences with form of prepositional verb phase with function of command as its dominant data.